HuR-Dependent Editing of a New Mineralocorticoid Receptor Splice Variant Reveals an Osmoregulatory Loop for Sodium Homeostasis - Ingrid Lema; Larbi Amazit; Khadija Lamribet; Jérôme Fagart; Anne Blanchard; Marc Lombès; Nadia Cherradi; Say Viengchareun (Scientific Reports, 2017)
Abstract Aldosterone and the Mineralocorticoid Receptor (MR) control hydroelectrolytic homeostasis and alterations of mineralocorticoid signaling pathway are involved in the pathogenesis of numerous human diseases, justifying the need to decipher molecular events controlling MR expression level. Here, we show in renal cells that the RNA-Binding Protein, Human antigen R (HuR), plays a central role in the editing of MR transcript as revealed by a RNA interference strategy. We identify a novel Δ6 MR splice variant, which lacks the entire exon 6, following a HuR-dependent exon skipping event. Using isoform-specific TaqMan probes, we show that Δ6 MR variant is expressed in all MR-expressing tissues and cells and demonstrate that extracelullar tonicity regulates its renal expression. More importantly, this splice variant exerts dominant-negative effects on transcriptional activity of the full-length MR protein. Collectively, our data highlight a crucial role of HuR as a master posttranscriptional regulator of MR expression in response to osmotic stress. We demonstrate that hypotonicity, not only enhances MR mRNA stability, but also decreases expression of the Δ6 MR variant, thus potentiating renal MR signaling. These findings provide compelling evidence for an autoregulatory feedback loop for the control of sodium homeostasis through posttranscriptional events, likely relevant in renal pathophysiological situations.